Influence of Employees 'Burnout on Work Motivation - Żaneta NEJMAN (Communications of International Proceedings, 2021)
The article discusses the concept of burnout, which is a decrease of motivation to work as a result of mental and physical exhaustion of their professional duties. Describes the behavior of employees, that may indicate a burnout process proceedings, as well as information on the causes of burnout and how to prevent this phenomenon. Drew attention to the need for proper management and supervision, as well as procedural and organizational solutions for the prevention of burnout. Also analyzed the level of burnout employees the production company. The research was designed to attempt to assess the impact of burnout syndrome to motivate employees. To analyze and evaluate these solutions served survey, the use of which has allowed us to formulate concrete proposals.
Keywords: Human Resource Management; Motivation; Burnout